PELAKSANAAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Andrew Shandy Utama (JCH (Jurnal Cendekia Hukum), 2018)
One of the goals of the state as mandated by the 1945 Constitution of the Republic of Indonesia is to improve the welfare of the people. Based on Article 74 Paragraph (1) of Law Number 40 of 2007, it is affirmed that companies that carry out their business activities in the field of natural resources and / or fields related to natural resources must carry out social and environmental responsibilities. How is the implementation of the corporate social and environmental responsibilities based on Law Number 40 of 2007 to improve the welfare of the community of Rumbai Pesisir Subdistrict of Pekanbaru City? The research method used in this research is socio-legal research. The results of this research that the corporate social and environmental responsibility programs on the community economy that have been carried out by PT Chevron Pacific Indonesia are called Local Business Development. The corporate social and environmental responsibility program for the community economy that has been carried out by PT Asia Forestama Raya, namely the creation of traditional markets managed by the community. The conclusion is that the government and the community can utilize the corporate social and environmental responsibility programs as an alternative source of business capital to improve the economy and welfare of the people in the Rumbai Pesisir Subdistrict of Pekanbaru City.